Incidence, factors, and disparities related to cancer among Black individuals in Canada: A scoping review. Issue 3 (27th November 2022) - Cénat, Jude Mary; Dromer, Élisabeth; Darius, Wina Paul; Dalexis, Rose Darly; Furyk, Sarah Elizabeth; Poisson, Hannah; Mansoub Bekarkhanechi, Farid; Shah, Muhammad; Diao, David Guangyu; Gedeon, Andi Phaelle; Lebel, Sophie; Labelle, Patrick R.
Abstract: Background: In Canada, two of five individuals will be diagnosed with cancer in their lifetime and one in four will die from this disease. Given the disparities observed in health research among Black individuals, we conducted a scoping review to analyze the state of cancer research in Canadian Black communities regarding prevalence, incidence, screening, mortality, and related factors to observe advances and identify gaps and disparities. Methods: A comprehensive search strategy was developed and executed in December 2021 across 10 databases (e.g., Embase). Of 3451 studies generated by the search, 19 were retained for extraction and included in this study. Results: Studies were focused on a variety of cancer types among Black individuals including anal, breast, cervical, colorectal, gastric, lung, and prostate cancers. They included data on incidence, stage of cancer at diagnosis, type of care received, diagnostic interval length, and screening. A few studies also demonstrated racial disparities among Black individuals. This research reveals disparities in screening, incidence, and quality of care among Black individuals in Canada. Conclusions: Given the gaps observed in cancer studies among Black individuals, federal and provincial governments and universities should consider creating special funds to generate research on this important health issue. Plain language summary: Important gaps were observed on research on cancer among Black communities in Canada. Studies included in the scoping review highlights disparities in screening, incidence, and quality of care among Black individuals in Canada. Abstract : Important gaps were observed on research on cancer among Black communities in Canada. Studies included in this scoping review highlight disparities in screening, incidence, and quality of care among Black individuals in Canada.